Capture efficiency and trophic adaptations of a specialist and generalist predator: A comparison - Michálek, Ondřej; Petráková, Lenka; Pekár, Stano (Ecology and evolution, 2017)
Specialist true predators are expected to exhibit higher capture efficiencies for the capture of larger and dangerous prey than generalist predators due to their possession of specialized morphological and behavioral adaptations. We used an araneophagous spider (Lampona murina) and a generalist spider (Drassodes lapidosus) as phylogenetically related model species and investigated their realized and fundamental trophic niches and their efficacy with respect to prey capture and prey handling. The trophic niche of both species confirmed that Lampona had a narrow trophic niche with a predominance of spider prey (including conspecifics), while the niche of Drassodes was wide, without any preference. DNA analysis of the gut contents of Lampona spiders collected in the field revealed that spiders form a significant part of its natural diet. Lampona captured significantly larger prey than itself and the prey captured by Drassodes. As concerns hunting strategy, Lampona grasped the prey with two pairs of legs possessing scopulae, whereas Drassodes immobilized prey with silk. Lampona possess forelegs equipped with scopulae and a thicker cuticle similar to other nonrelated araneophagous spiders. Lampona fed for a longer time and extracted more nutrients than Drassodes. We show that specialized behavioral and morphological adaptations altogether increase the hunting efficiency of specialists when compared to generalists.
Keywords: morphology; trophic niche; Drassodes; Lampona; Araneae; cannibalism; NGS; Araneophagy